Genetic polymorphism of FSHβ and PPP1r11 gene in crossbred breeding bulls - SAYYED, S J; CHOPADE, M M; ALI, S SAJID; NANDEDKAR, P V; KEKAN, P M; KHARAWADKAR, M D (The Indian Journal of Animal Sciences, 2025)
One of the most important traits in animal production is fertility, which is an indicator of successful reproduction. Considering the importance of male fertility, the present investigation was carried out to identify FSH-β and PPP1R11 gene polymorphism in breeding bulls of Maharashtra. The amplified DNA fragments of FSH-β (313bp) and PPP1R1 (599bp) gene were digested using enzymes PstI and NcoI, respectively. FSH-β gene digested with enzyme Pst1 produced three different genotype AA (202bp, 99bp), AB (313bp, 202bp and 99bp) and BB (313 bp) with genotypic frequencies of 0.05, 0.16 and 0.78 respectively, whereas the frequency of A and B allele was 0.13 and 0.86, respectively. The PCR product of PPP1R11 was digested with enzyme NcoI revealed one cutting site and produced two fragments of 332bp and 267bp in all the animals. While the sequencing results of PPP1R111 revealed a transversion mutation T>G at position 186. The variations in both FSH-β and PPP1R11 genes can be exploited to improve fertility if studied for association with fertility and semen traits.